Potential neuroprotective effects of heat-killed Lactococcus lactis KC24 using SH-SY5Y cells against oxidative stress induced by hydrogen peroxide - Lim, Sung-Min (Food Sci Biotechnol, 2020)
The present study was an investigation of the neuroprotective effects of probiotic bacteria in SH-SY5Y neuroblastoma cells experiencing oxidative stress. The bacterial strains were: commercial Lactobacillus rhamnosus GG; two isolated bacterial strains (Lactobacillus delbrueckii KU200170 and Lactobacillus plantarum KU200661); and probiotic Lactococcus lactis KC24. To evaluate the neuroprotective effects of the bacteria, a conditioned medium (CM) was prepared using HT-29 cells cultured with the heat-killed probiotic strains. Of the bacterial strains tested, the oxidatively stressed SH-SY5Y cells were most viable when cultured with L. lactis KC24-CM. L. lactis KC24-CM promoted the expression of brain-derived neurotropic factor (BDNF) in the HT-29 cells. It also significantly increased BDNF expression and reduced the apoptosis-related Bax/Bcl-2 ratio in the oxidatively stressed SH-SY5Y cells. Therefore, L. lactis KC24 is a potential psychobiotic for use in the functional food industry.